Heart rate variability and increased risk for developing type 2 diabetes mellitus - Penčić- Popović, Biljana; Ćelić, Vera; Ćosić, Zoran; Pavlović- Kleut, Milena; Čaparević, Zorica; Kostić, Nada; Milovanović, Branislav; Šljivić, Aleksandra; Stojčevski, Biljana (Vojnosanitetski pregled, 2014)
Background/Aim. To our knowledge there are no data about the relationship between elevated risk for developing type 2 diabetes mellitus (DM2) and altered cardiac autonomic function. The aim of this study was to evaluate the association between heart rate variability (HRV) and slightly increased risk for DM2. Methods. We evaluated 69 subjects (50.0 ± 14.4 years; 30 male) without DM2, coronary artery disease and arrhythmias. The subjects were divided into two groups according to the Finnish Diabetes Risk Score (FINDRISC): group I (n = 39) included subjects with 12 > FINDRISC ≥ 7; group II (n = 30) subjects with FINDRISC < 7. HRV was derived from 24-h electrocardiogram. We used time domain variables and frequency domain analysis performed over the entire 24-h period, during the day (06–22 h) and overnight (22–06 h). Results. Standard deviation of the average normal RR intervals was significantly lower in the group with increased risk for DM2 compared to the group II (127.1 ± 26.6 ms vs 149.6 ± 57.6 ms; p = 0.035). Other time domain measures were similar in both groups. The group I demonstrated significantly reduced frequency domain measures, total power – TP (7.2 ± 0.3 ln/ms2 vs 7.3 ± 0.3 ln/ms2; p = 0.029), and low frequency – LF (5.9 ± 0.4 ln/ms2 vs 6.3 ± 0.6 ln/ms2; p = 0.006), over entire 24 h, as well as TP (7.1 ± 0.3 ln/ms2 vs 7.3 ± 0.3 ln/ms2; p = 0.004), very low frequency (6.2 ± 0.2 ln/ms2 vs 6.3 ± 0.2 ln/ms2; p = 0.030), LF (5.9 ± 0.4 ln/ms2 vs 6.2 ± 0.3 ln/ms2; p = 0.000) and high frequency (5.7 ± 0.4 ln/ms2 vs 5.9 ± 0.4 ln/ms2; p = 0.011) during the daytime compared to the group II. Nocturnal frequency domain analysis was similar between the groups. The low diurnal frequency was independently related to elevated risk for diabetes mellitus (beta = -0,331; p = 0.006). Conclusion. The obtained results suggest that even slightly elevated risk for developing diabetes mellitus may be related to impaired HRV.